2016
DOI: 10.17221/20/2015-swr
|View full text |Cite
|
Sign up to set email alerts
|

Leaching effect of rainfall on soil under four-year saline water irrigation

Abstract: Cucci G., Lacolla G., Mastro M. A., Caranfa G. (2016): Leaching effect of rainfall on soil under four-year saline water irrigation. Soil & Water Res., In the context of the overall competition for water resources it is important to understand the complex dynamics of crop water management including evapotranspiration, water quality, and leaching requirement, each of them depending on the site-specific conditions. The research started with grain maize and continued with sunflower, grain maize, and wheat, at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Notably, most of the rainfall in the study area is received during winter season which may generate higher leaching fraction due to less evapotranspiration demand and hence greater salt leaching effect. Cucci et al (2016) also found similar impact of winter season rainfall under the Mediterranean climate in a sandy loam soil. Overall, the seasonal salinity and average salinity (1.97 dS/m) during the entire period of current climate (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) remained below threshold (EC sw = 4.2 dS/m) for viticulture.…”
Section: Seasonal Irrigation and Salinity In The Current Climatesupporting
confidence: 60%
“…Notably, most of the rainfall in the study area is received during winter season which may generate higher leaching fraction due to less evapotranspiration demand and hence greater salt leaching effect. Cucci et al (2016) also found similar impact of winter season rainfall under the Mediterranean climate in a sandy loam soil. Overall, the seasonal salinity and average salinity (1.97 dS/m) during the entire period of current climate (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) remained below threshold (EC sw = 4.2 dS/m) for viticulture.…”
Section: Seasonal Irrigation and Salinity In The Current Climatesupporting
confidence: 60%
“…Besides, groundwater evaporation could be reflected via the capillary rise, which in turn reveals the mechanism involved in groundwater evaporation. In such areas, the salts in deep soil layers will move up to shallow layers driven by upward groundwater under evaporation; meanwhile, the salts will also probably be leached into groundwater under large amount of irrigation (Cucci et al 2016;Yang et al 2019). This interactive behavior ultimately causes soil salinization and groundwater pollution, which has become a main obstacle during sustainable agricultural development (Benini et al 2016;Xing and Ma 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other than estuaries, the elevated groundwater salinity can be observed in the regions where groundwater is in contact with evaporates formations, or mixed with high mineralized and deeper aquifers [8,9]. The discharges from industrial effluents containing dissolved salts, leachates of saline soils and the runoff of salt deposits such as halite or gypsum that is present in the sedimentary rocks also increase the amounts of total dissolved salts and thus lead to the formation of brackish water [10][11][12]. However, the primary contributing source of brackish surface water (e.g., brackish dam water) is the mixing of the saline water from the open wells and the fresh water as well as the flow from the saline aquifer sourced from pumping wells to the surface water [13].…”
Section: Introductionmentioning
confidence: 99%